The Project Management Paradigm / With 118 Figures - Burnett Ken (Springer, 1998)
This book is all about how projects should be managed and controlled, including people and tools. Preface, The Philosophy of Project Management, Elements of the Project Management Methodology, Quality Management and Testing, Systems Project Development Activities, Project Roles and Responsibilities, Project Initiation, Tools of Project Management, Project Control, Project and Stage Completion Activities, Summary, References, Index.